Case Report: Identification of a novel PRR12 variant in a Chinese boy with developmental delay and short stature - Liu, Zhengxia; Ding, Shuxia; Xu, Guangwei; Fang, Chunyan (Frontiers in Pediatrics, 2024)
Proline Rich 12 (PRR12) protein is primarily expressed in the brain and localized in the nucleus. The variants in the PRR12 gene were reported to be related to neuroocular syndrome. Patients with PRR12 gene presented with intellectual disability (ID), neuropsychiatric disorders, some congenital anomalies, and with or without eye abnormalities. Here, we report an 11-year-old boy with a novel PRR12 variant c.1549_1568del, p.(Pro517Alafs*35). He was the first PRR12 deficiency patient in China and presented with ID, short stature, and mild scoliosis. He could not concentrate on his studies and was diagnosed with attention deficit hyperactivity disorder (ADHD). The insulin-like growth factor 1 (IGH-1) was low in our patient, which may be the cause of his short stature. Patients with neuroocular syndrome are rare, and further exploration is needed to understand the reason for neurodevelopmental abnormalities caused by PRR12 variants. Our study further expands on the PRR12 variants and presents a new case involving PPR12 variants.